2005
DOI: 10.1093/humrep/dei169
|View full text |Cite
|
Sign up to set email alerts
|

Decline in fertility of mouse sperm with abnormal chromatin during epididymal passage as revealed by ICSI

Abstract: These results demonstrate that in mice with sperm chromatin abnormalities, the decline in fertility of sperm with ICSI occurs after the caput epididymis. The advantage of using caput epididymal sperm for ICSI in certain situations may be considered as an approach to be tested in human assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
5
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(109 citation statements)
references
References 28 publications
6
95
5
3
Order By: Relevance
“…To date, several studies have reported higher ICSI pregnancy rates using testicular vs. ejaculated spermatozoa (in most series, ejaculated spermatozoa were used in the initial ICSI cycles) in men with cryptozoospermia (Bendikson et al, 2008;Hauser et al, 2011;Ben-Ami et al, 2013). These clinical findings support experimental observations demonstrating that in animals with impaired spermatogenesis, post-testicular spermatozoa have poorer chromatin integrity than testicular spermatozoa (Suganuma et al, 2005). In contrast, other investigators have reported favorable ICSI outcomes with the use of ejaculated spermatozoa (fresh or frozen-thawed) in men with cryptozoospermia and/or comparable ICSI outcomes using testicular vs. ejaculated spermatozoa in these men (Koscinski et al, 2007;Amirjannati et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…To date, several studies have reported higher ICSI pregnancy rates using testicular vs. ejaculated spermatozoa (in most series, ejaculated spermatozoa were used in the initial ICSI cycles) in men with cryptozoospermia (Bendikson et al, 2008;Hauser et al, 2011;Ben-Ami et al, 2013). These clinical findings support experimental observations demonstrating that in animals with impaired spermatogenesis, post-testicular spermatozoa have poorer chromatin integrity than testicular spermatozoa (Suganuma et al, 2005). In contrast, other investigators have reported favorable ICSI outcomes with the use of ejaculated spermatozoa (fresh or frozen-thawed) in men with cryptozoospermia and/or comparable ICSI outcomes using testicular vs. ejaculated spermatozoa in these men (Koscinski et al, 2007;Amirjannati et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…The testes have substantial antioxidant systems, but once spermatozoa are released from the Sertoli cells and migrate from the seminiferous tubules to the epididymis, they become susceptible to oxidative stress [110]. DNA damage in testicular spermatozoa is threefold lower compared with ejaculated spermatozoa [111].…”
Section: Testicular Sperm Extractionmentioning
confidence: 99%
“…This protein can reduce H 2 O 2 and cellular hydroperoxides, and may play a role in oxidative injury [41]. There is now substantial evidence for oxidative injury in spermatozoa of infertile patients, which in turn leads to increased injury of the genome [42]. Another interesting protein that could have been included in this category is the product of PARK7, which we have included under the protein synthesis category (see above).…”
mentioning
confidence: 99%